Numerical simulation and experimental verification of vacuum directional solidification process for multicrystalline silicon. (June 2015) - Lv, Guoqiang; Chen, Daotong; Yang, Xi; Ma, Wenhui; Luo, Tao; Wei, Kuixianai; Zhou, Yang
Abstract: In this paper, a transient numerical model was applied to simulate the vacuum directional solidification (VDS) process of multicrystalline silicon (mc-Si) under different pulling-down rates, and the evolution of temperature distribution, thermal stresses and shape of solid/liquid (s/l) interface were simulated and analyzed. The experiments, such as the content and distribution of metal impurity, the crystal growth orientation and quality of mc-Si ingot were investigated to evaluate and validate the relationship between the thermal stresses and shape of s/l interface with simulation results. The results show that thermal stress, shape of interface s/l and temperature distribution in the silicon is determined by the thermal conditions in the furnace during the VDS process, and the crystal growth quality of mc-Si ingot relates closely to these factors. An appropriate pulling-down rate can satisfy thermal conditions to provide ideal temperature gradient in the silicon with lower thermal stresses and suitable s/l interface. We found that the mc-Si ingot produced by VDS process with pulling-down rate of 10 μm s −1 had a larger grain size, a vertical columnar structure and an ideal efficiency of the impurity removal. Highlights: Investigations into vacuum directional solidification process for multicrystalline silicon were conducted. Proper thermal condition for high-quality crystal production can be obtained by adjusting the growth rate. The simulation and experimental results were in accord with each other.